Prolonged sitting reduces cerebral oxygenation in physically active young adults - Baker, Brett D.; Castelli, Darla M. (Frontiers in Cognition, 2024)
Introduction: Physical activity is known to enhance cognitive functioning across the lifespan, yet the effects of sedentary behaviors on cognitive functioning remain unclear. The purpose of this study was to determine how an acute daily bout of prolonged sitting influenced working memory, inhibitory control, and cerebral oxygenation (HbO2) in a sample of healthy young adults. Methods: Forty-one young adults (aged between 18-30 years of age) participated in an exploratory design intended to establish a control standard for determining how an acute two hour bout of prolonged sitting influenced working memory, inhibitory control, and HbO2. The Flanker task, Simon task, and Delayed Match to Sample were utilized to assess inhibitory control and working memory, respectively, while functional near-infrared spectroscopy assessed HbO2.Participants were further subdivided into a physically active (Active) group and a physically inactive group (Inactive) based on self-reported physical activity participation. Paired sample ttests were used to determine any changes in working memory, inhibitory control, and HbO2 from pre-to-post and between groups. Results: There were no differences in working memory or inhibitory control reaction time following prolonged sitting for the entire sample (p>0.05) or between activity groups (p>0.05). There was a significant reduction in Flanker accuracy postprolonged sitting for both the congruent (p<0.05) and incongruent (p<0.05) conditions. For those in the Inactive group, there was no difference in HbO2 concentrations post-prolonged sitting.Those in the Active group exhibited a significant reduction in HbO2 during the Flanker Task following prolonged sitting (p<0.05). Conclusions: An acute bout of daily prolonged sitting significantly reduced HbO2 in physically active young adults but not in inactive young adults.We recommend that future studies examining the effects of sedentary behaviors on microvasculature include an objective assessment of physical fitness and a direct measure of physical activity patterns and consider these values when assigning participants to the intervention condition.